Sharenting and the legal availability of the image of a sick minor (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The essay addresses the legal, ethical, and social implications of sharing images of sick minors online, in light of personality rights and parental responsibility. The publication of content – by parents, healthcare professionals, or organizations – depicting children in states of suffering raises complex issues regarding the protection of their identity, privacy, and dignity. The contribution considers the need to balance adults’ freedom of expression with the best interests of the minor, reviewing established jurisprudential guidelines and analyzing critical aspects related to commercial exploitation and instrumentalization within the context of fundraising and public awareness campaigns. The experience of the project “IMA-GO! Share Them with Care!” promoted by Fondazione Maruzza is as an example of normative nudging aimed at increasing awareness about the protection of childhood in the digital space.
Keywords: Sharenting; image; parental responsibility; dignity